Inflation targeting, debt, and the Brazilian experience, 1999 to 2003 - Giavazzi, Francesco; Goldfajn, Ilan; Herrera, Santiago (MIT Press, 2005)
How Brazil's monetary and fiscal policies survived a series of severe economic shocks and the policy lessons for other countries. Inflation targeting--when central bank policies set specific inflation rate objectives--is widely used by both developed and developing countries around the world (although not by the United States or the European Central Bank). This collection of original essays looks at how Brazil's policy of inflation targeting, coupled with a floating exchange rate, survived a series of severe economic shocks and examines the policy lessons that can be drawn from Brazil's experience. After a successful start in early 1999, Brazil's policy regime had to manage mounting difficulties, including a sudden reversal of capital flows and its effects on the exchange rate and public debt, the contagion of Argentina's severe economic problems, a domestic energy crisis, and the political uncertainty of the 2002 presidential campaign. The contributors, prominent Brazilian and international economists, draw important lessons from Brazil's experience, including the necessity of accompanying monetary policy with fiscal improvement, the trade-offs involved in dollar-linked debt, the importance of fiscal institutions in an emerging market economy, and the importance of keeping inflation under control.